2013
DOI: 10.1097/mlr.0b013e3182a95dd1
|View full text |Cite
|
Sign up to set email alerts
|

Successes of a National Study of the Chronic Disease Self-Management Program

Abstract: This National Study of CDSMP (National Study) demonstrates the successful translation of CDSMP into widespread practice and its potential for helping the nation achieve the triple aims of health care reform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
213
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(221 citation statements)
references
References 14 publications
7
213
0
1
Order By: Relevance
“…Therefore, our study findings need to be tempered due to the possibility of methodological confounds such as unaccounted group demographic and health differences at baseline, relatively small sample sizes, and better awareness among those in a clinical trial or high quality routine diabetes care that emphasizes the importance of glycemic control. For example, participants in this study were, on average, younger than those studied in other recent CDSMP studies [23,29] . Additionally, the controls in this study appeared slightly healthier and better educated than their counterparts in the CDSMP intervention which might have made them more receptive to both clinical and community-based diabetes self-management and obesity prevention messages.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Therefore, our study findings need to be tempered due to the possibility of methodological confounds such as unaccounted group demographic and health differences at baseline, relatively small sample sizes, and better awareness among those in a clinical trial or high quality routine diabetes care that emphasizes the importance of glycemic control. For example, participants in this study were, on average, younger than those studied in other recent CDSMP studies [23,29] . Additionally, the controls in this study appeared slightly healthier and better educated than their counterparts in the CDSMP intervention which might have made them more receptive to both clinical and community-based diabetes self-management and obesity prevention messages.…”
Section: Discussionmentioning
confidence: 79%
“…It has therefore been implemented worldwide for several chronic conditions such as heart disease, lung disease, arthritis, and diabetes as well as evaluated in various settings including the United States, Canada, United Kingdom, Australia, New Zealand, Bangladesh, China, Hong Kong, and The Netherlands [13][14][15][16][17][18][19][20] . While the original CDSMP validation study found improvements in general health status, health behaviors, and healthcare utilization [10] , the findings of more recent studies from a variety of self-management programs have been inconsistent [5,[21][22][23][24][25][26][27] . A recent literature review of randomized controlled trials comparing self-management support interventions for general chronic diseases vs usual care revealed mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this education should be delivered across transitions in care so that self-management strategies are reinforced in health care and community settings. 6 Despite the promising evidence for self-management programs, referral to and enrollment in these programs is low. Research studies examining factors associated with the enrollment in self-management programs have reported enrollment rates ranging from 22.8% 8 to as high as 59.6%.…”
Section: Background and Significancementioning
confidence: 99%
“…HARC was established by the Health Foundation of South Florida in 2008 to make evidence-based programs such as EF, LHP, MOB, and HI available to older adults in three southeast counties of South Florida: Miami-Dade, Broward, and Monroe Counties. Little is known about the effectiveness of these programs (Batra, Melchior, Seff, Frederick, & Palmer, 2012;Ory et al, 2013Ory et al, , 2014.…”
Section: Limitationsmentioning
confidence: 99%